High school EFL teachers' self-assessment of their technological pedagogical content knowledge: A case study in An Giang : - Dương, Huỳnh Vân (Trường Đại học Cần Thơ, 2020)
The aim of the study is aim mainly to examine EFL high school teachers' self-assessment of their technological pedagogical content knowledge and how they currently use it in their English language teaching.